Vascular Endothelial Growth Factor Expression in Correlation with Stage Juvenile Nasopharyngeal Angiofibroma - Ifiq Budiyan Nazar; Yussy Afriani Dewi; Agung Dinasti Permana (Althea Medical Journal, 2021)
Background: Juvenile Nasopharyngeal Angiofibroma (JNA) is a benign tumor of mesenchymal tissue, originating from the stromal and blood vessels with dense collagen. However, JNA has a malignant tumor-like property because it can cause erosion of surrounding bone. Vascular Endothelial Growth Factor (VEGF) plays a role in the angiogenesis process. The expression of VEGF is the best marker to determine the occurrence of angiogenesis in JNA. This study aimed to determine the correlation between VEGF expression and JNA clinical stage. Methods: This was a cross-sectional correlational analytic observational study on medical records and paraffin blocks of all patients with JNA at Dr. Hasan Sadikin General Hospital Bandung during the period of 2016 to 2019. Immunohistochemistry examination of VEGF expressions was performed and VEGF expression was rated based on staining intensity, percentage distribution, and histoscore. Data were then analyzed using the Spearman correlation test.Results: Of 24 patients, 23 males and 1 female, 58% demonstrated a strong intensity of staining. The positivity of VEGF cell percentage was identified as 26–50% (n=6 patients), 51–75% (n=11), and >75% (n=7). The median VEGF histoscores were 2.5, 6.5, and 12 in JNA stage I, stage II, and stage 3, respectively, with the greater VEGF histoscore had a higher clinical stage with a correlation coefficient of (rs) 0.723 (p=0.002). Conclusions: There is a strong correlation between increased VEGF expression and JNA clinical stage. VEGF expression can be used as a prognostic factor of JNA.